Identification of Vibrio parahaemolyticus and Vibrio spp. Specific Outer Membrane Proteins by Reverse Vaccinology and Surface Proteome - Wang, Wenbin; Liu, Jianxin; Guo, Shanshan; Liu, Lei; Yuan, Qianyun; Guo, Lei; Pan, Saikun (Frontiers in Microbiology, 2021)
Discovery of outer membrane proteins (OMPs) with desirable specificity and surface availability is a fundamental challenge to develop accurate immunodiagnostic assay and multivalent vaccine of pathogenic Vibrio species in food and aquaculture. Herein 101 OMPs were systemically screened from 4831 non-redundant proteins of V. parahaemolyticus by bioinformatical predication of signaling peptides, transmembrane (TM) α-helix, and subcellular location. The sequence homology analysis with 32 species of Vibrio spp. and all the non-Vibrio strains revealed that 15 OMPs were conserved in at least 23 Vibrio species, including BamA (VP2310), GspD (VP0133), Tolc (VP0425), OmpK (VP2362), OmpW (VPA0096), LptD (VP0339), Pal (VP1061), flagellar L-ring protein (VP0782), flagellar protein MotY (VP2111), hypothetical protein (VP1713), fimbrial assembly protein (VP2746), VacJ lipoprotein (VP2214), agglutination protein (VP1634), lipoprotein (VP1267), Chitobiase (VP0755); High adhesion probability of flgH, LptD, OmpK, and OmpW indicated they were potential multivalent Vibrio vaccine candidates. V. parahaemolyticus OMPs were found to share high homology with at least one or two Vibrio species, 19 OMPs including OmpA like protein (VPA073), CsuD (VPA1504), and MtrC (VP1220) were found relatively specific to V. parahaemolyticus. The surface proteomic study by enzymatical shaving the cells showed the capsular polysaccharides most likely limited the protease action, while the glycosidases improved the availability of OMPs to trypsin. The OmpA (VPA1186, VPA0248, VP0764), Omp (VPA0166), OmpU (VP2467), BamA (VP2310), TolC (VP0425), GspD (VP0133), OmpK (VP2362), lpp (VPA1469), Pal (VP1061), agglutination protein (VP1634), putative iron (III) compound receptor (VPA1435) have a better availability on the cell surface.